Epidemiological characteristics and influencing factors of acute leukemia in children and adolescents and adults: a large population-based study - Shuojie Liu; Bin Hu; Jiaqin Zhang (Hematology)
Objective: To assess the epidemiological characteristics and prognostic factors of acute leukemia (AL) in children and adolescents, and make comparisons between pediatric and adult patients.Methods: This retrospective cohort study enrolled AL patients from the Surveillance, Epidemiology, and End Results (SEER) 1975–2016. OS in children and adolescents and adults with AL was compared and analyzed separately by age and AL subtype.Results: Totally 61,694 AL patients were identified, with 45,411 (73.6%) adults and 16,283 (26.4%) children and adolescents. From 2000 to 2016, the incidence rates of AL [annual percent changes (APC) = 1.2, 95%CI = 0.9–1.6, P < 0.05] and acute lymphoblastic leukemia (ALL) (APC = 1.5, 95%CI = 1.1–1.8, P < 0.05) in children and adolescents were significantly increasing. For adults, AL (APC = 0.9, 95%CI = 0.3–1.5, P < 0.05), ALL (APC = 2.5, 95%CI = 2.0–3.1, P < 0.05) and acute myeloid leukemia (AML) (APC = 0.9, 95%CI = 0.4–1.5, P < 0.05) had significantly elevated incidence rates. Overall survival (OS) in children and adolescents with AL was significantly higher than that in adults with AL (log-rank P < 0.0001). OS in children and adolescents and adults with ALL, AML and AUL decreased with age (all log-rank P < 0.0001). Older age, male sex and black race were risk factors for the survival of children and adolescents and adults with ALL, AML and AUL.Conclusion: From 2000 to 2016, the incidence rates of AL in children and adolescents and adults were increasing. Children and adolescents with AL had significantly better OS than adults with AL, and OS declined with age in both children and adolescents and adults with ALL, AML and AUL.